KESIAPSIAGAAN K3RS DALAM PENANGGULANGAN BENCANA OLEH PERSONIL RUMAH SAKIT TK III DR R SOEHARSONO - Sapta Heru Purnama; Muhammad Hamdani Silaban; Puji Ayu Asri Sri Lestari; Mura Praja (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Banjarmasin is a flood-prone area with recurring incidents. Therefore, hospitals are urgently needed as one of the health facilities that are ready to respond when disasters strike. In managing this risk, SMK3RS is important for protecting staff and patients during disasters. The preparedness of hospital personnel is assessed based on three levels of competence, namely awareness level, mid-level, and advanced level. This qualitative case study research determined the research subjects using purposive sampling so that the quality of information was appropriate to the research context. Data analysis used coding techniques with the help of NVIVO software. The results of the study showed that Dr. R. Soeharsono Level III Hospital was at the advanced level in terms of K3RS preparedness for disaster management, with complete and adequate equipment, structured work procedures, and responsible leadership. There are still obstacles at the lower levels, where awareness-level personnel are still negligent. The mid-level is still hampered by ineffective education. This study recommends re-improvement by ensuring that there are written procedures during disasters and periodic education.